Pregabalin as a Treatment for Anxiety in Patients With Dementia With Lewy Bodies: A Case Series. Issue 3 (May 2020) - Segers, Kurt; Baxevani, Ermioni; Benoit, Florence; Meyts, Jean-Marie; Surquin, Murielle
Abstract: Background: Anxiety is a common and invalidating symptom of dementia with Lewy bodies (DLB). Methods: To evaluate the efficacy of pregabalin as a treatment for anxiety in DLB, we screened all medical files of our patients with DLB for the use of pregabalin in this context. Findings: Overall, pregabalin was well tolerated. Ten (62.5%) of 16 patients showed an improvement of anxiety, whereas in 3 of them, anxiety disappeared completely, at respectively 3, 11, and 22 months of follow-up, with total daily doses ranging from 75 to 150 mg. Positive response to pregabalin was associated with a significant reduction in benzodiazepine use. Conclusions: Pregabalin seems a useful and safe tool for treating anxiety in patients with DLB.